Correlations Between Awareness of Illness (Insight) and History of Addiction in Heroin-Addicted Patients - Maremmani, Angelo Giovanni Icro; Rovai, Luca; Rugani, Fabio; Pacini, Matteo; Lamanna, Francesco; Bacciardi, Silvia; Perugi, Giulio; Deltito, Joseph; Dell'Osso, Liliana; Maremmani, Icro (Frontiers in Psychiatry, 2012)
In a group of 1066 heroin addicts, who were seeking treatment for opioid agonist treatment, we looked for differences in historical, demographic and clinical characteristics, between patients with different levels of awareness of illness (insight). The results showed that, in the cohort studied, a majority of subjects lacked insight into their heroin-use behaviour. Compared with the impaired-insight group, those who possessed insight into their illness showed significantly greater awareness of past social, somatic and psychopathological impairments, and had a greater number of past treatment-seeking events for heroin addiction. In contrast with other psychiatric illnesses, the presence of awareness appears to be related to the passing of time and to the worsening of the illness. Methodologies to improve the insight of patients should, therefore, be targeted more directly on patients early in their history of heroin dependence, because the risk of lack of insight is greatest during this period.